Critical Text Edition and Assesment of Dawud Ibn Muhammad al-Qarisi's Commentary on isaghuji - ÖZPİLAVCI, FERRUH (CUMHURIYET UNIV, FAC THEOLOGY, 2017)
Living in the 18th century, a prolific era of Ottoman logic studies, Dawud al-Qarisi was a prominent scholar and logician who excelled in studies of Arabic Linguistics, Kalam, Hadith and Logic. Known as having a particular interest in Imam Birgivi (d. 981/1573) and his teaching, and serving as an instructor (mudarris) after living in Cairo and inheriting the scientific tradition of Egypt and the Maghrib, al-Qarisi's brilliancy in logic can be seen when his works on logic are examined. In this study, we prepare the critical text edition of al-Qarisi's Commentary on al-Abhari's short but famous treatise Isaghuji. The edition also includes reviewing and assessment of the work. After giving information about the life and works of al-Qarisi, we introduce and describe twelve works of logic authored by him which have not been previously identified or deeply studied. We have identified that al-Qarisi authored two other commentaries, one on Najm al din al-Katibi's famous al-Shamsiyya, the other on Sa'd al-Din al-Taftazani's Tandhib al-Mantiq wa al-Kalam. He also authored al-Isaghaji al-jadid as an alternative for Isaghaji. After giving information about all identified copies of the edited work, we present al-Qarisi's original ideas, critics and contributions to logic issues against such prominent logicians and commentators as Muhammad ibn Hamza al-Fanari (834/1431) and Husam al-din Hasan al-Kati (760/1359).
Keywords: Logic; Logic in Islamic Philosophy; Ottoman Thought; Logic in the Ottoman Thought; Commentary Tradition in Logic; isaghaji; Commentary on Isaghuji; Dawud al-Qarisi